Prophylactic use of tranexamic acid for reducing postpartum hemorrhage in vaginal delivery - Ginjupalli, Anusha; S. N., Anuradha; D., Joshi Suyajna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: The use of anti-fibrinolytic therapy has potential to reduce obstetric blood loss due to profound changes that take place in the fibrinolytic system during normal childbirth. Objective was to evaluate the efficacy of tranexamic acid in reducing postpartum hemorrhage (PPH) during normal labour. Methods: Patients who planned for normal delivery and fulfilling the inclusion criteria were recruited for the study. The pre-delivery parameters -pulse rate, blood pressure, Hb gm% and PCV% were measured for each patient. The study group received injection oxytocin (10 IU) and injection tranexamic acid (500 mg) slow intravenous route. The control group received injection oxytocin (10 IU) and placebo injection. Immediately after delivery of the anterior shoulder of the baby, when all the liquor was drained, Brasse-V drape is placed under the patient. Then the patient was given pre-weighed pads, which were weighed 2 hours post-partum. Final blood loss was calculated by combining amount of blood collected in the drape and blood absorbed by the pads. Results: The total number of patients studied was 300- equally distributed in both the groups. There was a significant increase in the pulse rate and decrease in blood pressure in the control group compared to the study group. The post-delivery haemoglobin and haematocrit were significantly reduced in the control group. The blood loss was significantly low in the study group. The need for other uterotonics, blood transfusion, and duration of hospital stay, were significantly low in study group. Conclusions: Tranexamic acid, when given prophylactically to the women with vaginal delivery who received prophylactic oxytocin, appears to reduce the blood loss effectively compared to placebo alone.